A double edged sword? Improvements in economic conditions over a decade in India led to declines in undernutrition as well as increases in overweight among adolescents and women - Young, Melissa F.; Nguyen, Phuong Hong; Tran, Lan Mai; Avula, Rasmi; Menon, Purnima (American Society for Nutrition, 2020)
This study examined the national and state trends for BMI and identified the determinants of underweight and overweight/obesity among adolescent girls and women.